The Configuration of Incentives in Small and Medium-Sized Content Platform Enterprises Under the Normalization of COVID-19 - Zhou, Yingying; Chen, Jianbin; Cheng, Baodong (Frontiers in Public Health, 2022)
The COVID-19 pandemic has made the advantages of online knowledge communities with cross-space, time, interpersonal, and other characteristics fully demonstrated. Exploring the configurations of platform incentives to improve knowledge collaboration performance can provide a reference for the efficient and sustainable development of the platforms under the normalization of the COVID-19 pandemic. With the help of the fuzzy set qualitative comparative analysis method, taking the social Q&A platform enterprises as an example, this study analyzed the configurations of platform incentives for the high knowledge collaborative performance from the dimensions of market incentives and social incentives, and the heterogeneity of knowledge capital appreciation and social capital appreciation is also discussed. The results show that each of the platform incentives (virtual currency, cash benefit, community reputation, social identity, skill training, and communication) does not constitute a necessary condition for high performance. There are four and three types of configurations for intellectual capital appreciation and social capital appreciation, respectively. The important findings are that nearly 30% of users may participate in knowledge production based on pure economic benefits, and there may be so-called “get the best deal” behavior. Social identity, community reputation, and skill training have an important incentive effect on knowledge collaboration. Communication supplemented by a little economic incentives can significantly promote the appreciation of social capital.